P233 A pilot diagnostic cardio-respiratory breathlessness clinic: can a symptom-based approach achieve an earlier diagnosis?. (15th November 2016) - Valero-Sanchez, I; Khatri, S; Nicolson, W; Seth, H; Walton, R; Jackson, DP; Steiner, MC; Evans, RA
Abstract : Introduction: We aimed to compare the time to diagnosis and treatment between a combined cardio-respiratory diagnostic breathlessness clinic (BC) and usual specialist outpatient care (UC) in patients with chronic breathlessness referred from primary care. Methods: We surveyed patients with undifferentiated chronic breathlessness referred to secondary care outpatient cardiology and respiratory services during March 2015 (UC). Subsequently, we implemented a fortnightly pilot breathlessness clinic (BC) between August 2015 and January 2016 using existing referrals to either cardiology or respiratory specialties. Patients were seen by either a consultant cardiologist or respiratory physician, reviewed by a physiotherapist, and discussed by the MDT at the end of clinic. The investigations performed in primary care were documented and where needed the following investigations were completed for the BC: haemoglobin, brain natriuretic peptide, spirometry, electrocardiogram, chest radiograph, Nijmegen questionnaire, screening for anxiety and depression symptoms and a physical activity questionnaire. Time to diagnosis, physiotherapy, treatment and discharge were measured and compared with UC. Patients were requested to complete a patient experience questionnaire. Results: Table 1 shows the results of UC compared to the BC. 35% of referrals from primary care reported ≤1 investigation and only 28% had had spirometry performed. The MRC dyspnea scale grade distribution in the BC was MRC1 = 4%, MRC2 = 30%, MRC3 = 37%, MRC4 = 22%, MRC5 = 7%. Co-morbidity was common with over >80% of patients having at least two diagnoses contributing to their breathlessness. Dysfunctional breathing was the commonest primary and secondary diagnosis. 18.5% of patients in the BC could have been diagnosed in primary care. 18.5% were originally referred to the incorrect specialty and in nearly 30% of patients referrals to the other specialty were potentially avoided due to the MDT discussion. Only one third of patients required specialist tests to secure their diagnosis. All patients rated their experience as 'excellent'. Conclusions: Our pilot diagnostic breathlessness clinic reduced time to diagnosis and treatment, and avoided further between-specialty outpatient appointments. However, our results demonstrate the need for symptom-based breathlessness pathways starting in primary care to utilise simple investigations prior to referral to specialist clinics. Reference: Valero I, et al . Abstract accepted ERS, 2016.